CHALLENGES FACED BY PROSECUTORS IN THE ADMINISTRATION OF JUSTICE IN PAKISTAN - IQRA KHALIL; AHMED USMAN; AAISHA AMJAD (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Criminal justice system is one of the fundamental formal structures to maintain a peaceful society. It covers the nature of offence committed, the procedures to deal with crime and criminal, the type of punishment for offender, and protection to the victim in a society. The system of criminal justiceconsists of three major institutions includingpolice, prosecution and judiciary. Unfortunately, the institution of prosecution is found to be weak and ineffective in the administration of justice in Pakistan. Through in-depth interviews conducted with the prosecutors, the present study highlights the challenges faced by the prosecutors in Pakistani context of criminal justice. The study found that the prosecutors in Pakistan feel vulnerable between two powerful institutions of police and judiciary. They have no significant authority to contribute towards transparent access to justice. They are not only powerless but also face various personal, administrative and procedural issues while serving as prosecutors. The present study is a useful contribution in policy making and academic sphere of criminal justice system, especially in the Pakistani context.